1984
DOI: 10.1021/jo00189a010
|View full text |Cite
|
Sign up to set email alerts
|

Electron donor-acceptor quenching and photoinduced electron transfer for coumarin dyes

Abstract: The fluorescence of 7-aminocoumarins is quenched by a variety of organic electron donors or acceptors in acetonitrile. In general, donors with half-wave oxidation potentials less positive than 1.0 V vs. SCE and acceptors with reduction potentials less negative than -1.5 V vs. SCE are candidates for diffusion limited quenching of coumarin singlet states. Profiles of quenching rates are consistent with calculated free energies for electron transfer between excited coumarins and donors or acceptors. In flash phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 1 publication
7
53
0
Order By: Relevance
“…The free energies of photo-electron transfer process (DG ET ) between the azo dyes and the quenchers are found to be about À19 kcal/mol. All of the calculated free energy changes are below the value of À5 kcal/mol (the ''rule of thumb'') [53]. These data can be taken as proofs that photoelectron transfer process occurs between the quenchers and sensitizer molecules and contact radical ion pairs are generated.…”
Section: Measurements and Fluorescence Quenching Experimentsmentioning
confidence: 72%
“…The free energies of photo-electron transfer process (DG ET ) between the azo dyes and the quenchers are found to be about À19 kcal/mol. All of the calculated free energy changes are below the value of À5 kcal/mol (the ''rule of thumb'') [53]. These data can be taken as proofs that photoelectron transfer process occurs between the quenchers and sensitizer molecules and contact radical ion pairs are generated.…”
Section: Measurements and Fluorescence Quenching Experimentsmentioning
confidence: 72%
“…The RFI value of 1f, with the strongest electron-withdrawing nitro group, was comparable with that of 1b, with an electron-donating methyl group. This prominent decrease in 1f may be attributed to the nonemissive twisted ICT (TICT) excited state, [39][40][41][42][43] where push-pull p-electron systems between a methoxyl group at the 6-position and a nitro group at the 3-position in a molecule must be fully separated in polar solvent such as acetonitrile. Rettig and Klock reported that the very weak fluorescence of 6-aminocoumarin with a stronger electron-donating amino group than the methoxyl group was attributed to this TICT between the amino group and coumarin ring.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation potentials of the amines ͕E(A/A ϩ )͖ in TX100 micellar solutions were estimated from the reported values in acetonitrile solutions after applying a suitable correction for the micellar media. [47][48][49][50] …”
Section: Methodsmentioning
confidence: 99%